2021
DOI: 10.21037/atm-20-3376
|View full text |Cite
|
Sign up to set email alerts
|

Perception of femininity and attractiveness in Facial Feminization Surgery

Abstract: Background: Facial Feminization Surgery (FFS) alters bone and soft tissue to feminize facial features of transgender females. This study aims to evaluate perceptions of femininity, attractiveness, and ideal surgical outcomes in transgender females, non-transgender females and plastic surgeons. Methods:The data was extracted from a survey of transgender females (n=104), non-transgender females (n=192) (completion rate of 48.4%) and plastic surgeons who performed FFS (n=23) (survey response rate of 31.5%). Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…For instance, the perception of femininity can vary widely depending on cultural or societal norms, and thus there is no universal standard for what constitutes a “feminine” face 16,17 . Second, transgender females’ perceptions of facial femininity and attractiveness may differ from non-transgender females 18 . The outcomes of FFS are highly dependent on the individual’s unique facial features and the specific procedures performed, making it challenging to compare patients and surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the perception of femininity can vary widely depending on cultural or societal norms, and thus there is no universal standard for what constitutes a “feminine” face 16,17 . Second, transgender females’ perceptions of facial femininity and attractiveness may differ from non-transgender females 18 . The outcomes of FFS are highly dependent on the individual’s unique facial features and the specific procedures performed, making it challenging to compare patients and surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Second, transgender females' perceptions of facial femininity and attractiveness may differ from non-transgender females. 18 The outcomes of FFS are highly dependent on the individual's unique facial features and the specific procedures performed, making it challenging to compare patients and surgeons. Despite these obstacles, most studies have reported high levels of patient satisfaction following facial feminization.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, other studies have noted differences in the perception of facial femininity between surgeons and transgender females. 17 Eye tracing technology has shown that transgender patients fixate on the fronto-orbital complex and mandible when assessing gender. 18 Further studies are needed to assess the degree of bony changes needed to establish optimal feminine facial qualities and the relationship to patient-reported outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Ching et al [12 ▪▪ ] report an interesting study on gender perception by comparing the perception of three facial features which have not been shown by previous studies to contribute to ideal surgical outcomes. The facial features evaluated were nasal tip width, angle of the supratip break, and gonial angle.…”
Section: Gender Perceptionmentioning
confidence: 99%